Pengaruh Model Discovery Learning Dipadu Lesson Study terhadap Hasil Belajar Mahasiswa Pendidikan Biologi: (The Effect of Discovery Learning Model Combined with Lesson Study on Learning Outcomes of Biology Education Students) - Lely Mardiyanti (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
Combining the learning model with lesson study (LS) can increase the effect of the model in achieving the desired learning outcomes. The purpose of this pre-experimental research is to determine the effect of the discovery learning model combined with LS on the learning outcomes of Biology Education Students. This research was conducted for 1 semester on 30 students who took Plant Physiology Course in the Undergraduated Program of Biology Education, Universitas Negeri Malang using one-group pretestâ€“posttest design. Data on learning outcomes were obtained through essay tests (pretest and posttest) and analyzed using paired t tests. The results of the paired t test inform that there is a big difference in student learning outcomes before (M = 37.5, SD = 13.3) and after learning using the discovery learning model combined with LS (M = 77, SD = 13), t(29) = 18.2, p < 0.001, d = 3.3. Thus, the application of the discovery learning model combined with LS has a major effect on the learning outcomes of Biology Education students in Plant Physiology Course. Key words: Discovery Learning, Lesson Study, and Learning Outcomes Â Abstrak Memadukan model pembelajaran dengan lesson study (LS) dapat meningkatkan pengaruh model dalam mencapai hasil belajar yang diinginkan. Tujuan dari penelitian pre-eksperimental ini yaitu mengetahui pengaruh model discovery learning dipadu LS terhadap hasil belajar Mahasiswa Pendidikan Biologi. Penelitian ini dilakukan selama 1 semeter pada 30 mahasiswa yang menempuh Mata Kuliah Fisiologi Tumbuhan di Program Studi S-1 Pendidikan Biologi, Universitas Negeri Malang menggunakan one-group pretestâ€“posttest design. Data hasil belajar diperoleh melalui tes esai (pretes dan postes) dan dianalisis menggunakan uji t berpasangan. Hasil uji t berpasangan menginformasikan bahwa terdapat perbedaan besar pada hasil belajar siswa sebelum sebelum (M = 37,5, SD = 13,3) dan setelah pembelajaran menggunakan model discovery learning dipadu LS (M =77, SD = 13), t(29) = 18,2, p < 0,001, d = 3,3. Sehingga, penerapan model discovery learning dipadu LS memiliki pengaruh besar terhadap hasil belajar mahasiswa Pendidikan Biologi pada Mata Kuliah Fisiologi Tumbuhan. Kata kunci: Discovery Learning, Lesson Study, dan Hasil Belajar